2015
DOI: 10.1016/s2214-109x(15)00195-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a congregation-based intervention on uptake of HIV testing and linkage to care in pregnant women in Nigeria (Baby Shower): a cluster randomised trial

Abstract: Summary Background There is a dearth of effective community-based interventions to increase HIV testing and uptake of antiretroviral therapy (ART) among pregnant women in hard–to-reach resource-limited settings. We assessed whether a faith-based intervention, the Healthy Beginning Initiative (HBI), would increase uptake of HIV testing and ART among pregnant women as compared to health facility referral. Methods This trial was conducted in southeast Nigeria, between January 20, 2013, and August 31, 2014. Eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 27 publications
0
75
0
Order By: Relevance
“…Previously published results showed that women in churches randomized to the intervention arm were more likely to be screened for HIV, linked to care, and on ARV therapy during pregnancy. 35 Of the 3002 women who participated in HBI, 2254 received HIV testing [IG = 1514 (92%), CG = 740 (55%)]. A total of 72 of the 2254 women tested (3.19%) were identified to be HIV infected and gave birth to 69 live infants (including 1 set of twins).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published results showed that women in churches randomized to the intervention arm were more likely to be screened for HIV, linked to care, and on ARV therapy during pregnancy. 35 Of the 3002 women who participated in HBI, 2254 received HIV testing [IG = 1514 (92%), CG = 740 (55%)]. A total of 72 of the 2254 women tested (3.19%) were identified to be HIV infected and gave birth to 69 live infants (including 1 set of twins).…”
Section: Resultsmentioning
confidence: 99%
“…We present a brief synopsis of HBI here; however, details of the study protocol, sample size, and power analysis are published elsewhere. 29,34 Enrollment began in January 2013 and was completed by September 2013. Follow-up of enrolled participants was completed by August 2014.…”
Section: Methodsmentioning
confidence: 99%
“…60,61 Successful approaches at the community level include utilization of existing socially accepted community-based infrastructure (eg, churches) 62 and the use of lay counselors 21,6365 to build trust and acceptability, mitigate stigma, and serve as an acceptable entry point into the HIV continuum. Other community-level interventions, including availability of counseling resources in the community and the provision of community-based testing services with or without peer or lay counselors (including door-to-door, self-testing, mobile-testing, workplace-based, school-based, church-based, etc.)…”
Section: Hiv Testing and Counselingmentioning
confidence: 99%
“…Community leaders are important to the provision of health information and education, and may influence behavioural and social norms in culturally appropriate ways (Leban 2011;USAID 2015). Mobilising faith leaders, in particular, has been instrumental in addressing the HIV epidemic globally, including the promotion of access to prevention of mother to child transmission services during prenatal care (Chi and Stringer 2015;Ezeanolue et al 2015;Widmer et al 2011). Leban (2011) argues that their views on well-being and their stature enable them to influence the supply and demand sides of health services.…”
Section: Challenges For Antenatal Care In Sub-saharan Africamentioning
confidence: 99%